Identification of a Novel Frame-Shift Mutation in PRSS1 Gene in Han Patients with Autoimmune Pancreatitis - Gao, F.; Li, Y.; Wang, C.; Zhuang, Z.; Liu, Q.C.; Chen, J.; Hong, G.; Xu, Z. (Current Molecular Medicine, 2014)
Objective: To detect mutations of trypsinogen gene (PRSS1) in patients with autoimmune pancreatitis (AIP) and to determine the underlying pathogenesis. Methods: DNA sequencing was used to detect full-length of PRSS1, cystic fibrosis transmembrane conductance regulator (CFTR), and pancreatic secretory trypsin inhibitor (SPINK1) genes mutations in an AIP family and a sporadic case and 520 normal controls. Furthermore, a mutant-expressing system was constructed for functional confirmation. Results: For the first time, we report a deletion mutation at exon 2 of PRSS1 gene (IVS 2 +56_60 del CCCAG) which encoded a truncated PRSS1 protein without trypsinogen activation peptide (TAP). Vitro functional study suggested the identified mutation would result in loss of PRSS1 activity. Mutant trypsinogen activated at a faster rate than wild-type trypsinogen in the autoactivation experiment. Histopathologic examination revealed the ratio of IgG4/IgG-positive plasma cells exceeded 0.455 in pancreas, and the patients responded to glucocorticoids. Conclusion: PRSS1: IVS 2 +56_60 del CCCAG is a noval mutant which may contribute to AIP pathogenesis.
Keywords: IVS 2 +56_60 del CCCAG mutation